Tips for permanent education in mental health in primary care guided by the Institutional Socio-clinic - Larissa de Almeida Rézio; Cinira Magali Fortuna; Flávio Adriano Borges (Universidade de São Paulo, 2019)
Objective: to analyze a process of Permanent Education in Health about mental health with Family Health teams. Method: research-intervention performed with 20 workers from two teams of the Family Health Strategies. Semi-structured interviews and 12 reflection meetings were carried out with each team. The principles of Institutional Socio-clinic were used to guide the meetings and the analysis of the data. Results: seven beaconing tips were identified for the Process of Permanent Education in Health: effects produced from the choices of inclusion of the management in the planning of the meetings, revealing established ways of working; attention to non-control in training movements; use of restitution at meetings, reducing stiffness and tensions; attention to the institutions that cross us; analysis of the facilitator's involvement in the training, redirecting behaviors and attitudes; problematization about the object, instrument and purpose, which favored the reflection about the mental health care and to learn to facilitate and experience the Permanent Education in Health in the act of making. Conclusions: socio-clinic assisted the experience of facilitating in-service training, pointing out tips for the collective construction of contextualized, reflexive and problematizing knowledge.